2021
DOI: 10.3390/diseases9040074
|View full text |Cite
|
Sign up to set email alerts
|

Patient Heterogeneity in Acute Myeloid Leukemia: Leukemic Cell Communication by Release of Soluble Mediators and Its Effects on Mesenchymal Stem Cells

Abstract: Acute myeloid leukemia (AML) is an aggressive bone marrow malignancy, and non-leukemic stromal cells (including mesenchymal stem cells, MSCs) are involved in leukemogenesis and show AML-supporting effects. We investigated how constitutive extracellular mediator release by primary human AML cells alters proteomic profiles of normal bone marrow MSCs. An average of 6814 proteins (range 6493−6918 proteins) were quantified for 41 MSC cultures supplemented with AML-cell conditioned medium, whereas an average of 6715… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…CK2 is a regulatory molecule at all three levels of networks [56,61], and the function of CK2 as a regulator of Toll-like receptor 4 (TLR4)-NFκB pathway signaling can be used as an example of how CK2 inhibition influences AML cells through effects on all three levels of networks . The various network effects of TLR4 and its CK2-regulated downstream target NFκB summarized in Figure 1: leukemogenesis/chemosensitivity is thereby modulated through three interacting networks: (i) Cross-talking intracellular signaling pathways (yellow) [9,[12][13][14]16,22,71,[75][76][77][78], (ii) the local extracellular microenvironment (extracellular matrix and cytokines; green) [76,[79][80][81][82][83], and (iii) the cellular network with interactions between the leukemic cells and their neighboring non-leukemic endothelial cells [84,[86][87][88][89][90][91], MSC [80,92,93], osteoblasts [76,94,95] and immunocompetent cells [96][97][98][99][100][101] (all in blue). Thus, the effects of TLR4/NFκB intracellular signaling are modulated by CK2-mediated phosphorylation of the common target NFκB.…”
Section: Effects Of Ck2 Inhibition On Intracellular Signaling Extrace...mentioning
confidence: 99%
See 2 more Smart Citations
“…CK2 is a regulatory molecule at all three levels of networks [56,61], and the function of CK2 as a regulator of Toll-like receptor 4 (TLR4)-NFκB pathway signaling can be used as an example of how CK2 inhibition influences AML cells through effects on all three levels of networks . The various network effects of TLR4 and its CK2-regulated downstream target NFκB summarized in Figure 1: leukemogenesis/chemosensitivity is thereby modulated through three interacting networks: (i) Cross-talking intracellular signaling pathways (yellow) [9,[12][13][14]16,22,71,[75][76][77][78], (ii) the local extracellular microenvironment (extracellular matrix and cytokines; green) [76,[79][80][81][82][83], and (iii) the cellular network with interactions between the leukemic cells and their neighboring non-leukemic endothelial cells [84,[86][87][88][89][90][91], MSC [80,92,93], osteoblasts [76,94,95] and immunocompetent cells [96][97][98][99][100][101] (all in blue). Thus, the effects of TLR4/NFκB intracellular signaling are modulated by CK2-mediated phosphorylation of the common target NFκB.…”
Section: Effects Of Ck2 Inhibition On Intracellular Signaling Extrace...mentioning
confidence: 99%
“…The observations described above are mainly based on studies of the overall AML cell population, but several characteristics of the total hierarchically organized AML cell Targeting of complex biological networks in AML by CK2 inhibition; TLR4/CK2/NFκB interactions as an example of the complexity of CK2 targeting. NFκB is a common target for downstream TLR4 signaling and CK2-mediated phosphorylation; leukemogenesis/chemosensitivity is thereby modulated through three interacting networks: (i) Cross-talking intracellular signaling pathways (yellow) [9,[12][13][14]16,22,71,[75][76][77][78], (ii) the local extracellular microenvironment (extracellular matrix and cytokines; green) [76,[79][80][81][82][83], and (iii) the cellular network with interactions between the leukemic cells and their neighboring non-leukemic endothelial cells [84,[86][87][88][89][90][91], MSC [80,92,93], osteoblasts [76,94,95] and immunocompetent cells [96][97][98][99][100][101] (all in blue). Thus, the effects of TLR4/NFκB intracellular signaling are modulated by CK2-mediated phosphorylation of the common target NFκB.…”
Section: Effects Of Ck2 Inhibition On Intracellular Signaling Extrace...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent proteomic study, we investigated the effect of the constitutive AML cell release of soluble mediators on the proteomic profile of normal mesenchymal stem cells (MSCs) [ 35 ]. We observed that the AML effect on the global MSC proteomic profiles differed between patients, and we detected two main AML patient subsets with regard to the AML effect on normal MSCs.…”
Section: Tlr4 In Acute Myeloid Leukemiamentioning
confidence: 99%
“… The constitutive AML cell mediator release cytokine release profile and thereby the context of the TLR4 induced cytokine response will differ between patients [ 24 , 25 , 26 ]. The effect of TLR4 targeting on MSCs/osteoblasts seems to depend on the biological context ( Section 5.1 and Section 5.2 ); due to the functional heterogeneity of AML cells with regard to their constitutive protein release the biological context/microenvironment of the osteoblasts and thereby the effect of TLR4 targeting will differ between AML patients [ 25 , 35 , 45 , 112 , 113 , 114 , 115 , 116 ]. However, although the heterogeneity between patients with regard to constitutive cytokine release by the AML cells may influence the MSC-osteoblast differentiation, the AML supporting MSC effect is observed independent of this patient heterogeneity [ 3 ].…”
Section: Pharmacological Targeting Of Tlr4; a Possible Therapeutic St...mentioning
confidence: 99%